A new amino acid substitution (Ala-205-Phe) in acetolactate synthase (ALS) confers broad spectrum resistance to ALS-inhibiting herbicides - Brosnan, James T. (Planta, 2015)
This is a first report of an Ala-205-Phe substitution in acetolactate synthase conferring resistance to imidazolinone, sulfonylurea, triazolopyrimidines, sulfonylamino-carbonyl-triazolinones, and pyrimidinyl (thio) benzoate herbicides. Resistance to acetolactate synthase (ALS) and photosystem II inhibiting herbicides was confirmed in a population of allotetraploid annual bluegrass (Poa annua L.; POAAN-R3) selected from golf course turf in Tennessee. Genetic sequencing revealed that seven of eight POAAN-R3 plants had a point mutation in the psbA gene resulting in a known Ser-264-Gly substitution on the D1 protein. Whole plant testing confirmed that this substitution conferred resistance to simazine in POAAN-R3. Two homeologous forms of the ALS gene (ALSa and ALSb) were detected and expressed in all POAAN-R3 plants sequenced. The seven plants possessing the Ser-264-Gly mutation conferring resistance to simazine also had a homozygous Ala-205-Phe substitution on ALSb, caused by two nucleic acid substitutions in one codon. In vitro ALS activity assays with recombinant protein and whole plant testing confirmed that this Ala-205-Phe substitution conferred resistance to imidazolinone, sulfonylurea, triazolopyrimidines, sulfonylamino-carbonyl- triazolinones, and pyrimidinyl (thio) benzoate herbicides. This is the first report of Ala-205-Phe mutation conferring wide spectrum resistance to ALS inhibiting herbicides. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00425-015-2399-9) contains supplementary material, which is available to authorized users.